Evaluation of Acute and Sub-Acute Dermal Toxicity Studies of Ethanolic Leaf Extract of Lawsonia Inermis in Rats - Zahi, Ali Khairullah; Hamzah, Hazilawati; Shaari, Mohd Rosly; Widodo, Riyanto Teguh; Johnny, Lucy; M.M, Noordin; Sithambaram, Shanmugavelu (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Lawsonia inermis is one of the most significant plants used in traditional medicine. However, many details of the dermal toxicity of L. inermis remain unknown. The objective of this study is to evaluate the in vivo acute and sub-acute dermal toxicity of ethanolic extract of L. inermis leaves. In acute experiment, a total of 20 rats were divided into four groups of five rats. A total of 30 rats were divided into five groups of six rats for the sub-acute experiment. The extract at a single dose of 2000 and 5000 mg/kg of body weight did not produce treatment-related signs of toxicity or mortality in all rats tested during the 14-day observation period. However, in a repeated dose 28-day study, the application of 500, 1000 and 2000 mg/kg of body weight/day of leaves extract revealed no significant change (p > 0.05) in bodyweight, haematological and biochemical parameters compared with the control group. Similarly, gross pathology and histopathology examinations of liver, kidneys, and skin did not reveal any morphological alteration. Overall, the results show that the close application of L. inermis leaves extract did not have any critically dangerous impact on rats. Subsequently, the concentrate may be employed for pharmaceutical plans.